Analysis of emerging psychosocial risk factors in a municipal service – working conditions beyond the obvious. (1st January 2012) - Silva, Catarina; Costa, Cláudia; Saraiva, David
The aim of this study is to examine the less visible side effects of work on health – psychosocial risk factors – among 351 workers divided into two groups – white-collar and blue-collar – both belonging to a municipal public service. A Portuguese survey was used to collect the subjective perception of work constraints and characteristics, as well as, health and well-being complaints. A descriptive statistical analysis was performed for all questions in the inquiry and logistic regression models were used to find out associations between working conditions and both health and well-being complaints. The white-collar group results showed that, besides the office work common characteristics, this group is exposed to an intensification phenomenon with negative impacts on health – sleep disturbances, pain and emotional reactions. The blue-collar group results showed that this group is exposed not only to environmental and physical exertion constraints, but also to work pace and relationship constraints which have physical, psychological and behavioural effects on individuals.